2011
DOI: 10.1021/cm2003269
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Electronic Nature of Aggregation-Induced Emission Luminogens with Enhanced Hole-Transporting Property

Abstract: Triphenylamine (TPA) is a well-known hole-transporting material but suffers aggregation-caused emission quenching in the solid state. Tetraphenylethene (TPE), on the other hand, is an archetypal luminogen that shows the phenomenon of aggregation-induced emission (AIE). In this work, TPA is attached to the TPE core as peripheral group to generate new AIE luminogens with enhanced hole-transporting property. The TPA-TPE adducts, named 1-[4′-(diphenylamino)biphenyl-4-yl]-1,2,2-triphenylethene (TPATPE) and 1,2-bis[… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
98
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 186 publications
(104 citation statements)
references
References 45 publications
(18 reference statements)
5
98
0
1
Order By: Relevance
“…Intermolecular π···π interactions, 20 however, can have dramatic impact on the solid-state luminescence properties and can lead to red shifts in the emission spectra. 7 In I B crystal, the [Au 2 L 2 ] 2+ helicates are packed into head-to-tail fashion to form columnar stacks (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intermolecular π···π interactions, 20 however, can have dramatic impact on the solid-state luminescence properties and can lead to red shifts in the emission spectra. 7 In I B crystal, the [Au 2 L 2 ] 2+ helicates are packed into head-to-tail fashion to form columnar stacks (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…36 Eisenberg and co-workers have found that a weakly emissive thiouracil (tuH) 15 gold(I) complex, [Au 2 (μ-tuH)(μ-dppm)](CF 3 CO 2 ) after gentle crushing exhibits intense blue luminescence as a result of a molecular structure modification occurred upon a solid-state chemical reaction (release of CF 3 CO 2 H). 40 However, up to now, only two gold(I) complexes that exhibit reversible 20 mechanochromic luminescence have been reported. 42, 43 Ito and Sawamura reported the [(F 5 C 6 Au) 2 (μ-1,4-CNC 6 H 4 )] complex that shows a change in its luminescence colour from blue to yellowgreen upon grinding and subsequent reversion to its original emission colour upon solvent treatment.…”
Section: Introductionmentioning
confidence: 99%
“…This AIE phenomenon can be explained by the restriction of non-radiative vibrational relaxation processes in the aggregated solid state. Representative examples of AIE-active fluorophores include siloles, [6][7][8][9] cyanostilbenes, [10][11][12] o-carborane derivatives [13][14][15][16][17] and tetraphenylethenes [18][19][20][21][22][23] . Some of these fluorophores have proved useful as non-doped emission layers in fluorescent OLEDs.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these fluorophores have proved useful as non-doped emission layers in fluorescent OLEDs. [19][20][21][22][23] However, these OLEDs can only utilize singlet excitons for electroluminescence (EL) and the resulting internal EL quantum efficiency (η int ) is limited to 25% because of the inherent spin-statistical limitation of electrical excitation, which generates radiative singlet excitons and non-radiative triplet excitons in a 1:3 ratio. 24 Recent research efforts in our group 25 and others [26][27][28][29][30] have focused on exploring AIE-active materials that simultaneously exhibit thermally activated delayed florescence [31][32][33][34][35][36][37][38][39] to harvest triplet excitons for EL via efficient reverse intersystem crossing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation